Implementation of Restorative Justice to Corruption Crimes According to The Perspective of Indonesian Criminal Law And Islamic Law - Erdianto Effendi; Fitri Wahyuni; Nilma Suryani (Nagari Law Review, 2023)
Restorative settlement seems to be the trend of criminal law enforcement today. The restorative settlement model has been practiced by the criminal justice sub-system ranging from the police, prosecutors to the courts. Restorative settlement is the concept of a settlement where the interested parties meet to resolve the issue together how to resolve the consequences of the violation in the interest of the common future as well. Nowadays new ideas are emerging that the crime of corruption can be solved through restoratife justice. However, there is a need for studies on the application of restoratife justice for corruption crimes both from the aspect of Indonesian criminal law and from the aspect of Islamic law. This research is a normative research that is descriptive-comparative. That is to provide an overview of the application of Restorative Justice in corruption crimes by comparing them according to Indonesian criminal law and Islamic law. The data used are secondary data consisting of primary, secondary and tertiary legal materials. The analysis stage starts from data collection, data processing and finally the presentation of data by pulling deductively knots. The application of restoratife justice in the typist because it has no juridical legal basis, the prosecutor or the police and even the court has no right to represent the victims of state losses, but the community is more entitled. If you really want a restorative application to the crime of corruption, then there is a need for mekenism that must involve public figures more broadly. Similarly, in Islam, corruption is not the same as murder which allows for diyat. Corruption is closer to theft where the law is to cut hands.